18q12.3‐q21.1 microdeletion detected in the prenatally alcohol‐exposed dizygotic twin with discordant fetal alcohol syndrome phenotype. Issue 4 (25th February 2020) - Kahila, Hanna; Marjonen, Heidi; Auvinen, Pauliina; Avela, Kristiina; Riikonen, Raili; Kaminen‐Ahola, Nina
Abstract: Background: A pair of dizygotic twins discordantly affected by heavy prenatal alcohol exposure (PAE) was reported previously by Riikonen, suggesting the role of genetic risk or protective factors in the etiology of alcohol‐induced developmental disorders. Now, we have re‐examined these 25‐year‐old twins and explored genetic origin of the phenotypic discordancy reminiscent with fetal alcohol syndrome (FAS). Furthermore, we explored alterations in DNA methylation profile of imprinting control region at growth‐related insulin‐like growth factor 2 ( IGF2 ) /H19 locus in twins' white blood cells (WBC), which have been associated earlier with alcohol‐induced genotype‐specific changes in placental tissue. Methods: Microarray‐based comparative genomic hybridization (aCGH) was used to detect potential submicroscopic chromosomal abnormalities, and developmental as well as phenotypic information about twins were collected. Traditional bisulfite sequencing was used for DNA methylation analysis. Results: Microarray‐based comparative genomic hybridization revealed a microdeletion 18q12.3‐q21.1. in affected twin, residing in a known 18q deletion syndrome region. This syndrome has been associated with growth restriction, developmental delay or intellectual deficiency, and abnormal facial features in previous studies, and thus likely explains the phenotypic discordancy between the twins. We did not observe association between WBCs' DNA methylation profile and PAE, but interestingly, a trend of decreased DNA methylation at the imprinting control region was seen in the twin with prenatal growth retardation at birth. Conclusions: The microdeletion emphasizes the importance of adequate chromosomal testing in examining the etiology of complex alcohol‐induced developmental disorders. Furthermore, the genotype‐specific decreased DNA methylation at the IGF2/H19 locus cannot be considered as a biological mark for PAE in adult WBCs. Abstract : Methylation profiles of imprinting control region at the IGF2/H19 locus in white blood cells of prenatally alcohol‐exposed adult twins and control women.